Serum Concentration of VEGF and PDGF-AA in Patients with Active Thyroid Orbitopathy before and after Immunosuppressive Therapy - Nowak, M.; Marek, B.; Karpe, J.; Kos-Kudla, B.; Sieminska, L.; Kajdaniuk, D.; Treszer, M. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Introduction: Thyroid orbitopathy (TO) is the most frequent extrathyroid manifestation of Graves’ disease. The aim of this study was to evaluate the serum concentration of Vascular Endothelial Growth Factor (VEGF), Plated-Derived Growth Factor-AA (PDGF-AA) in the blood of patients with active OT before and after immunosuppressive therapy.Patients and Methods: The study was performed in group of 39 patients with clinically active TO (Group A) in euthyroid (n=18, Group A I) and hyperthyroid (n=21, Group A II) stage of Graves’ disease in moderate or severe stage of TO. Control group consist of 20 healthy age-matched control subjects. Concentration of studied proangiogenic factors in serum samples were measured by an enzyme linked immunosorbent assay (ELISA) before (group A) and after (group A1) intensive pulse methylprednisolone treatment and one month after the end of additional oral methylprednisolone treatment (Group A2).Results: We have found significant increased serum levels of VEGF in patients with TO (regardless to treatment) when compared with control group (542.4±328.1 pg/ml vs. 94.6±55.3 pg/ml, p=0.0002) and increased serum levels of PDGF-AA in patients before treatment (3 173.6±1 480.3 pg/ml) in comparison with controls (1 768.9±520.0 pg/ml) and patients after intensive pulse methyloprednisolone treatment (2 325.9±1 456.8 pg/ml). One month after the end of additional oral methylprednisolone treatment (Group A2) concentration of PDGF-AA still decreased and were was not significant difference with value in control group (1 853.1±795.4 vs. 1 769.9±520.0 pg/ml, p=0.99). Serum concentration of VEGF was still significantly higher compared with control. We have not observed difference in serum concentration of studied proangiogenic factors between patients in euthyroid or hyperthyroid stage of Graves’ disease.Conclusions: Results of the present study confirm the fact that angiogenesis could play a role in pathogenesis of thyroid orbitopathy.
Keywords: Graves’ orbitopathy; proangiogenic factors; methylprednisolone treatment